Thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability and preparation method thereof
Thermoplastic polyimide-polyurea corrosion-resistant materials were prepared by step-by-step polymerization, and internal hydrogen bonds were used to improve chain interactions, solving the compatibility problem of PUA-PI composite materials, achieving tight interface bonding and performance improvements.
Patent Information
- Application Number
- CN202510272238.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There are compatibility problems in the composite process of PUA-PI composite materials, resulting in the intimate bonding of the material interface and the expected comprehensive performance cannot be achieved.
Thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability are prepared by step-by-step polymerization method, and internal hydrogen bonds are used to improve chain interactions, control the self-assembly procedures within and between hydrogen bonds, and maintain a dense microstructure.
It improves the hardness and toughness of PI, and at the same time gives PUA special functions such as high temperature resistance and corrosion resistance, solves the problem of material compatibility and achieves tight bonding of the material interface.
Smart Images

Figure CN119751812A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of elastomer composite materials, in particular to a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability and a preparation method thereof. Background Art
[0002] Polymer materials are indispensable materials in daily life, transportation, industry and other fields. They are widely used in automobile and military industries due to their light weight, strong plasticity and good insulation. Polymer materials include plastics, rubber and fibers. In recent years, polyurea (PUA) and polyimide (PI) as new polymer materials have attracted wide attention due to their excellent physical and chemical properties.
[0003] PUA is polymerized from isocyanate components and amino components. Currently, there are three known types of polyurea, namely aromatic polyurea, aliphatic polyurea and polyaspartic acid polyurea. The principle of the synthesis reaction is the reaction of semi-prepolymer with terminal amino polyether and amine chain extender, in which the semi-prepolymer is generated by isocyanate and polyether polyol. Due to the high activity of terminal amino polyether and the alkalinity of N atom, the reaction can be carried out in a short time without catalyst. The microstructure of PUA molecule is a cross-linked network structure formed by the reaction of alternating isocyanate and amine, which is manifested as alternating hard segments and soft segments, which makes PUA have high chemical stability and can resist the penetration, diffusion and erosion of corrosive media.
[0004] PI is a type of polymer containing an acid imide five-membered heterocyclic ring on the main chain. The large π bond structure of the aromatic ring in the polymer containing the phthalimide ring greatly improves the rigidity of the molecular chain and interacts with the heterocyclic structure to form a charge transfer complex (CTC). Compared with polymer materials with a carbon chain structure as the main chain, polyimide has greatly improved mechanical properties, solvent resistance, radiation stability, dielectric properties, etc., and has comprehensively expanded the application field of polymer materials. Its structure is shown in the figure: Polyimide structure diagram PI is one of the polymers with the best thermal properties. Its glass transition temperature is greater than 200°C and its thermal decomposition temperature is generally greater than 500°C. The thermal decomposition temperature of polyimide synthesized from biphenyl dianhydride and p-phenylenediamine exceeds 600°C. The heat resistance of polyimide depends on the rigidity of the main chain of the molecule and the interaction force between molecules. The greater the rigidity / interaction force, the more difficult the molecular chain movement is and the higher the glass transition temperature is.
[0005] In actual use, in some cases, PUA and PI alone will show obvious shortcomings, such as PI's hygroscopicity, high dielectric constant, hydrolysis under alkaline conditions, etc.; PUA's mechanical properties, heat resistance, lack of temperature resistance, and difficulty in application in extreme conditions. However, the composite material after the two are combined will produce a synergistic effect, which significantly improves the overall performance of PUA-PI. However, since PUA and PI have different chemical structures and affinities, there may be problems with material compatibility during the composite process, which may lead to loose interface bonding of the composite material, thus failing to achieve the expected comprehensive performance of the material. Summary of the invention
[0006] In order to solve the compatibility problem of PUA-PI composite materials, the present invention provides a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability and a method for preparing the same. The method is based on internal hydrogen bonds to improve chain interactions, and a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability (abbreviated as: PUA-PI corrosion-resistant material) is prepared by a step-by-step polymerization method. In the PUA-PI corrosion-resistant material prepared by this method, the presence of hydrogen bond donor atoms and hydrogen bond acceptor atoms in PUA and PI can well control the self-assembly process within and between hydrogen bonds, so that it maintains a dense microstructure, retains the original microphase separation structure of polyurea, and maintains a dense molecular gap, enhances barrier performance, solves the compatibility problem in the material composite process, and the interface of the composited materials is tightly bonded. Therefore, the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability and a method for preparing the same provided by the present invention can not only improve the hardness and toughness of PI, but also give PUA special functionality such as high temperature resistance and corrosion resistance.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention discloses a thermoplastic polyimide-polyurea corrosion-resistant material having thermal stability, which has the following structural formula: In the above formula: n is the average number of repeating units of polyimide, which is a positive integer; m is the average number of repeating units of polyurea, which is a positive integer.
[0008] The structural formula of X is ; The structural formula of Y is .
[0009] The present invention also relates to a method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material having thermal stability, comprising the following steps: (1) Preparation of polyimide nanopowder: The diamine monomer is dissolved in a solvent, and the dianhydride monomer is slowly added to obtain a high molecular weight polyamic acid through a condensation reaction, and then thermal imidization and dehydration are performed to form polyimide; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is solid-liquid separated to obtain an upper liquid, and finally the upper liquid is dried to obtain a polyimide nanopowder.
[0010] (2) Preparation of isocyanate prepolymer: freeze-drying the amino-terminated polyether to obtain a dehydrated amino-terminated polyether; Dissolving diisocyanate and polyimide nanopowders in a solvent and uniformly dispersing them by ultrasonication to obtain a diisocyanate / polyimide mixed solution; The dehydrated amino-terminated polyether is slowly added dropwise to the diisocyanate / polyimide mixed solution, stirred in an ice water bath for 2-3 hours, and then transferred to 80-90° C. and heated for 3-4 hours to obtain a polyimide / diisocyanate composite prepolymer; (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: The liquid amine chain extender is freeze-dried, and the dehydrated liquid amine chain extender is slowly added dropwise to the polyimide / diisocyanate composite prepolymer, reacted for more than 30 minutes, transferred to a mold, cured and solidified, to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0011] In the step (1), the dianhydride monomer is selected from one or a mixture of pyromellitic anhydride (PMDA) and bisanhydride (BTDA); the diamine monomer is selected from one or a mixture of 4,4'-diaminodiphenyl ether (ODA) and p-phenylenediamine (PDA); and the solvent is selected from butyrolactone.
[0012] In the step (1), the temperature of the polycondensation reaction is 60-70° C., and the reaction time is 2-3 hours.
[0013] In the step (1), the drying temperature of the thermal imidization is preferably 100-120° C., and the drying time is preferably 8 hours or more.
[0014] In the step (1), the ball milling treatment adopts a high-speed planetary ball mill, the revolution: rotation = 1:2, the ball milling speed is 350-550rpm, the material ball mass ratio is polyimide: solvent: ball milling ball = 1: (80-100): (200-300); the ball milling ball is preferably a zirconia ball.
[0015] In the step (1), the solid-liquid separation is preferably performed by centrifugation, and the centrifugation is performed using a high-speed refrigerated centrifuge at a centrifugal speed of 5000-5500 rpm.
[0016] In the step (1), the particle size of the polyimide nanopowder is 50-500 nm.
[0017] In the step (2), the amino-terminated polyether is preferably polyoxypropylene diamine.
[0018] In the step (2), the mass ratio of thermoplastic polyurea: polyimide nanopowder is 100: (0.1-2.0).
[0019] In the step (2), the ultrasonic dispersion is carried out for a period of more than 20 minutes.
[0020] In the step (2), the slow dripping speed is 0.1-0.5 mL / s, which is used to prepare the isocyanate prepolymer.
[0021] In the step (2), the diisocyanate is selected from aromatic diisocyanates and / or aliphatic diisocyanates; more preferably, it is a mixture of 2,4'-MDI (diphenylmethane-2,4'-diisocyanate) and 4,4'-MDI (diphenylmethane-4,4'-diisocyanate).
[0022] In the step (3), the liquid amine chain extender is preferably diethyltoluenediamine.
[0023] In the step (3), the stirring time is more than 30 minutes.
[0024] In the step (3), the drying temperature is preferably 80° C., and the curing time is preferably 48 hours or more.
[0025] In the method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability, all raw materials are added in amounts according to the reaction stoichiometric ratio.
[0026] The preparation route of the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability of the present invention is as follows: (1) Preparation of polyimide nanopowder (2) Preparation of isocyanate prepolymer (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability In the above structural formula, n is the average number of repeating units of polyimide, which is a positive integer, and m is the average number of repeating units of polyurea, which is a positive integer.
[0027] The above steps are only for clearer expression and are not intended to limit the order of the steps in the preparation process. The steps of the present invention can be implemented simultaneously without affecting the final effect.
[0028] The thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability and the preparation method thereof of the present invention provide a method for improving the mechanical properties of polyurea elastomers and imparting characteristic functionality thereto, and the advantages thereof are: (1) The present invention provides a method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability. The internal hydrogen bonds are used to improve the chain interactions, so that the mechanical properties of the polyurea elastomer are significantly improved. At the same time, the polyurea elastomer is endowed with functionality such as high temperature resistance, thereby solving the problems of insufficient mechanical properties of traditional elastomers and low practical applicability of thermal decomposition temperature.
[0029] (2) As a new type of special engineering polymer, polyimide has good thermal stability, corrosion resistance, toughness and damage resistance, and can be used in aviation, aerospace and other fields. However, since it is a flexible material, it cannot be used alone. The polyimide-reinforced polyurea elastomer composite material provided by the present invention has good mechanical properties, which enhances the engineering applicability of polyimide, especially in the field of building materials and special protection.
[0030] (3) The thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability provided by the present invention has a stable chemical structure. Polyimide is selected as a reinforcing agent to modify polyurea. The chain interaction is improved based on internal hydrogen bonds. Polyimide can be well dispersed in the polyurea molecules. The HH bonds between the polyurea molecules and the polyimide molecules make the molecular structure of the hybrid more compact, the intermolecular force is stronger, and the chemical properties are more stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The tensile strength performance experimental data of the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability in Examples 1 to 5 of the present invention and Comparative Example 1; Figure 2 The experimental data of the corrosion resistance of the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability in Example 3 and Comparative Example 1 of the present invention; (a) is the corrosion time and absorption rate correlation curve of Example 3; (b) is the corrosion time and absorption rate correlation curve of Comparative Example 1; Figure 3 The experimental data of impact resistance of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2 are shown in Table 1. (a) is the experimental data of tensile strength; (b) is the experimental data of elongation at break; Figure 4This is a thermogravimetric analysis image analysis of the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with embodiments.
[0033] The following content is combined with specific examples to illustrate the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability and its preparation method in the present invention.
[0034] In the following examples, the instrument used to test the impact resistance of the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability prepared by the present invention is an XJJY-50 simply supported beam impact tester purchased by Chengde Kecheng Testing Machine Co., Ltd. The polyurea elastomer is cut into a square film of 100mm×12.5mm and adhered to an aluminum sheet of 100mm×12.5mm×2mm for impact testing. An impact pendulum with an impact energy storage of 15J is selected.
[0035] In the following embodiments, the instrument used to test the tensile strength of the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability prepared by the present invention is a GX-SF001 computer servo tensile testing machine purchased by Shenzhen Shared Instrument Equipment Co., Ltd. The polyurea elastomer film is cut into standard pieces with a gauge length of 10 mm, and the tensile strength test is performed on it at a tensile speed of 500 mm / min, and a stress-strain curve is plotted.
[0036] In the following embodiments, the instrument used for ball milling in the preparation process of the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability of the present invention is a F-P2000 high-speed planetary ball mill purchased by Hunan Fucas Experimental Instrument Co., Ltd., with a revolution: rotation = 1:2, a ball milling speed of 350~550rpm, and a material ball mass ratio of polyimide: solvent: zirconia ball = 1:80~100:200~300.
[0037] In the following embodiments, the instrument used for centrifugal treatment during the preparation of the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability of the present invention is a TGL20MW desktop large-capacity high-speed refrigerated centrifuge purchased by Hunan Hirsch Instrument Equipment Co., Ltd., with a centrifugal speed of 5000~5500rpm and a temperature of 25°C.
[0038] In the following examples, the instrument used for thermogravimetric analysis of the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability of the present invention is a DTA-50 high-temperature differential thermal analyzer purchased from Shimadzu Corporation of Japan, with the setting parameters of 1200°C and a scanning rate of 10°C / min.
[0039] In the following example, the detailed description of the thermally stable thermoplastic polyimide-polyurea corrosion resistant material includes the following steps: Example 1 A method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability comprises the following steps: (1) Preparation process of nano polyimide: Aromatic diamine is dissolved in butyrolactone, and pyromellitic anhydride is slowly added dropwise, and the mixture is placed in a 65°C oil bath for heating reaction for 2-3 hours, and then the mixture is taken out and placed in a mold, and then dried at 110°C for 8 hours or more for dehydration to obtain a polyimide solid; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is centrifuged to obtain a centrifuged upper layer liquid, and finally the centrifuged upper layer liquid is dried to obtain a polyimide nanopowder.
[0040] (2) Preparation of isocyanate prepolymer: 10g of polyoxypropylene diamine was freeze-dried to obtain dehydrated polyoxypropylene diamine. 3.42g of 2,4'-MDI and 4,4'-MDI isomers and 0.015g of polyimide nanopowder were dissolved in 15mL~25mL of N,N-dimethylformamide, and ultrasonically dispersed for 20min to obtain an aromatic diisocyanate / polyimide mixed solution. The dehydrated polyoxypropylene diamine was slowly added dropwise to the aromatic diisocyanate. After the addition was completed, the mixture was stirred in an ice-water bath for 2~3h, then transferred to an 85℃ oil bath and heated in an oil bath for 3~4h to obtain a polyimide / aromatic diisocyanate composite prepolymer.
[0041] (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: Take 1.63g of diethyltoluenediamine and freeze-dry it. Slowly add the dehydrated diethyltoluenediamine dropwise into the polyimide / aromatic diisocyanate prepolymer, stir for 30 minutes and then transfer it to a mold. Curing it in an oven and curing it at 80°C for 48 hours or more to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0042] The mass fraction of polyimide in the prepared thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability is 0.1wt%.
[0043] Example 2 A method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability comprises the following steps: (1) Preparation process of polyimide: Dissolve aromatic diamine in butyrolactone, slowly add pyromellitic anhydride, put it in a 65℃ oil bath to heat and react for 2~3h, take it out and put it in a mold, dry it at 110℃ for 8h or more to dehydrate it, and obtain a polyimide solid; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is centrifuged to obtain the upper liquid after centrifugation, and the centrifugation uses a high-speed refrigerated centrifuge with a centrifugal speed of 5000~5500rpm. Finally, the upper liquid after centrifugation is dried to obtain polyimide nanopowder. Among them, the ball milling treatment uses a high-speed planetary ball mill, revolution: rotation = 1:2, the ball milling speed is 350~550rpm, and the mass ratio of the ball is, polyimide: solvent: zirconium oxide ball = 1: (80~100): (200~300).
[0044] (2) Preparation of isocyanate prepolymer: 10g of polyoxypropylene diamine was freeze-dried to obtain dehydrated polyoxypropylene diamine. 3.42g of 2,4'-MDI and 4,4'-MDI isomers and 0.075g of polyimide nanopowder were dissolved in 15mL~25mL of N,N-dimethylformamide and dispersed by ultrasound for 20min. The dehydrated polyoxypropylene diamine was slowly added dropwise to 2,4'-MDI and 4,4'-MDI isomers. After the addition was completed, it was stirred in an ice water bath for 2~3h, then transferred to an 85℃ oil bath pot and heated in the oil bath for 3~4h to obtain a polyimide / aromatic diisocyanate composite prepolymer.
[0045] (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: 1.63 g of diethyltoluenediamine was freeze-dried, and the dehydrated diethyltoluenediamine was slowly added dropwise to the polyimide / aromatic diisocyanate composite prepolymer, stirred for 30 minutes, and then transferred to a mold, cured in an oven, and cured at 80° C. for 48 hours or more to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0046] The mass fraction of polyimide in the prepared thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability is 0.5wt%.
[0047] Example 3 A method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability comprises the following steps: (1) Preparation process of polyimide: Aromatic diamine is dissolved in butyrolactone, and pyromellitic anhydride is slowly added dropwise, and the mixture is placed in a 65°C oil bath for heating reaction for 2-3 hours, and then the mixture is taken out and placed in a mold, and then dried at 110°C for 8 hours or more for dehydration to obtain a polyimide solid; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is centrifuged to obtain a centrifuged upper layer liquid, and finally the centrifuged upper layer liquid is dried to obtain a polyimide nanopowder.
[0048] (2) Preparation of isocyanate prepolymer: 10g of polyoxypropylene diamine was freeze-dried to obtain dehydrated polyoxypropylene diamine. 3.42g of 2,4'-MDI and 4,4'-MDI isomers and 0.12g of polyimide nanopowder were dissolved in 15mL~25mL of N,N-dimethylformamide and dispersed by ultrasound for 20min. The dehydrated polyoxypropylene diamine was slowly added dropwise to 2,4'-MDI and 4,4'-MDI isomers. After the addition was completed, it was stirred in an ice-water bath for 2~3h, then transferred to an 85℃ oil bath pot and heated in the oil bath for 3~4h to obtain a polyimide / aromatic diisocyanate composite prepolymer.
[0049] (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: 1.63 g of diethyltoluenediamine was freeze-dried, and the dehydrated diethyltoluenediamine was slowly added dropwise to the polyimide / aromatic diisocyanate composite prepolymer, stirred for 30 minutes, and then transferred to a mold, cured in an oven, and cured at 80° C. for 48 hours or more to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0050] The mass fraction of polyimide in the prepared thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability is 0.8wt%.
[0051] Example 4 A method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability comprises the following steps: (1) Preparation process of polyimide: Aromatic diamine is dissolved in butyrolactone, and pyromellitic anhydride is slowly added dropwise, and the mixture is placed in a 65°C oil bath for heating reaction for 2-3 hours, and then the mixture is taken out and placed in a mold, and then dried at 110°C for 8 hours or more for dehydration to obtain a polyimide solid; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is centrifuged to obtain a centrifuged upper layer liquid, and finally the centrifuged upper layer liquid is dried to obtain a polyimide nanopowder.
[0052] (2) Preparation of isocyanate prepolymer: 10g of polyoxypropylene diamine was freeze-dried to obtain dehydrated polyoxypropylene diamine. 3.42g of 2,4'-MDI and 4,4'-MDI isomers and 0.15g of polyimide nanopowder were dissolved in 15mL~25mL of N,N-dimethylformamide and dispersed by ultrasound for 20min. The dehydrated polyoxypropylene diamine was slowly added dropwise to 2,4'-MDI and 4,4'-MDI isomers. After the addition was completed, it was stirred in an ice-water bath for 2~3h, then transferred to an 85℃ oil bath pot and heated in the oil bath for 3~4h to obtain a polyimide / aromatic diisocyanate composite prepolymer.
[0053] (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: 1.63 g of diethyltoluenediamine was freeze-dried, and the dehydrated diethyltoluenediamine was slowly added dropwise to the polyimide / aromatic diisocyanate composite prepolymer, stirred for 30 minutes, and then transferred to a mold, cured in an oven, and cured at 80° C. for 48 hours or more to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0054] The mass fraction of polyimide in the prepared thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability is 1.0wt%.
[0055] Example 5 A method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability comprises the following steps: (1) Preparation process of polyimide: Aromatic diamine is dissolved in butyrolactone, and pyromellitic anhydride is slowly added dropwise, and the mixture is placed in a 65°C oil bath for heating reaction for 2-3 hours, and then the mixture is taken out and placed in a mold, and then dried at 110°C for 8 hours or more for dehydration to obtain a polyimide solid; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is centrifuged to obtain a centrifuged upper layer liquid, and finally the centrifuged upper layer liquid is dried to obtain a polyimide nanopowder.
[0056] (2) Preparation of isocyanate prepolymer: 10g of polyoxypropylene diamine was freeze-dried to obtain dehydrated polyoxypropylene diamine. 3.42g of 2,4'-MDI and 4,4'-MDI isomers and 0.3g of polyimide nanopowder were dissolved in 15mL~25mL of N,N-dimethylformamide and dispersed by ultrasound for 20min. The dehydrated polyoxypropylene diamine was slowly added dropwise to 2,4'-MDI and 4,4'-MDI isomers. After the addition was completed, it was stirred in an ice-water bath for 2~3h, then transferred to an 85℃ oil bath pot and heated in the oil bath for 3~4h to obtain a polyimide / aromatic diisocyanate composite prepolymer.
[0057] (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: 1.63 g of diethyltoluenediamine was freeze-dried, and the dehydrated diethyltoluenediamine was slowly added dropwise to the obtained polyimide / aromatic diisocyanate composite prepolymer, and after stirring for 30 minutes, it was transferred to a mold, cured in an oven, and solidified at 80°C for 48 hours to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0058] The mass fraction of polyimide in the prepared thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability is 2.0wt%.
[0059] Comparative Example 1 The preparation method of the polyurea corrosion-resistant material comprises the following steps: (1) Preparation of isocyanate prepolymer: Freeze-dry 10g of polyoxypropylene diamine to obtain dehydrated polyoxypropylene diamine. Dissolve 3.42g of 2,4'-MDI and 4,4'-MDI isomers in 15mL~25mL of N,N-dimethylformamide and disperse them by ultrasound for 20min. Slowly drop the dehydrated polyoxypropylene diamine into 2,4'-MDI and 4,4'-MDI isomers. After the dropwise addition is completed, stir in an ice-water bath for 2~3h, then transfer to an 85℃ oil bath and heat in the oil bath for 3~4h to obtain an isocyanate prepolymer.
[0060] (2) Preparation of polyurea corrosion-resistant materials: The diethyltoluenediamine was freeze-dried, and the dehydrated diethyltoluenediamine was slowly added dropwise to the isocyanate prepolymer, and after stirring for 30 minutes, it was transferred to a mold, and placed in an oven at 80° C. for curing for 48 hours to obtain a polyurea corrosion-resistant material.
[0061] Comparative Example 2 A method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability comprises the following steps: (1) Preparation process of nano polyimide: Aromatic diamine is dissolved in butyrolactone, and pyromellitic anhydride is slowly added dropwise, and the mixture is placed in a 65°C oil bath for heating reaction for 2-3 hours, and then the mixture is taken out and placed in a mold, and then dried at 110°C for 8 hours or more for dehydration to obtain a polyimide solid; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is centrifuged to obtain a centrifuged upper layer liquid, and finally the centrifuged upper layer liquid is dried to obtain a polyimide nanopowder.
[0062] (2) Preparation of isocyanate prepolymer: 10g of polyoxypropylene diamine was freeze-dried to obtain dehydrated polyoxypropylene diamine. The dehydrated polyoxypropylene diamine was slowly added dropwise to 3.42g of aromatic diisocyanate. After the addition was completed, the mixture was stirred in an ice-water bath for 2-3h, then transferred to an 85°C oil bath and heated in the oil bath for 3-4h to obtain an aromatic diisocyanate prepolymer.
[0063] (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: Take 1.63g of diethyltoluenediamine and freeze-dry it. Dissolve the dehydrated diethyltoluenediamine and 0.015g of polyimide nanopowder in 15mL~25mL of N,N-dimethylformamide and disperse it by ultrasound for 20min to obtain a diethyltoluenediamine / polyimide mixed solution. Then slowly add it dropwise to the aromatic diisocyanate prepolymer, stir for 30min, transfer it to a mold, cure it in an oven, and cure it at 80℃ for 48h or more to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0064] The mass fraction of polyimide in the prepared thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability is 0.1wt%.
[0065] This example was difficult to solidify during the chain extension reaction, and the mechanical properties and corrosion resistance of the cured polyimide-polyurea corrosion-resistant material decreased significantly. The reason for this is that polyimide consumes part of the isocyanate group during the chain extension process, resulting in a decrease in the actual consumption of diethyltoluenediamine. The free diethyltoluenediamine exists in the form of monomers in the polyimide-polyurea corrosion-resistant material, affecting the uniformity of the polyimide-polyurea corrosion-resistant material.
[0066] Comparative Example 3 A method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability comprises the following steps: (1) Preparation process of nano polyimide: Aromatic diamine is dissolved in butyrolactone, and pyromellitic anhydride is slowly added dropwise, and the mixture is placed in a 65°C oil bath for heating reaction for 2-3 hours, and then the mixture is taken out and placed in a mold, and then dried at 110°C for 8 hours or more for dehydration to obtain a polyimide solid; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is centrifuged to obtain a centrifuged upper layer liquid, and finally the centrifuged upper layer liquid is dried to obtain a polyimide nanopowder.
[0067] (2) Preparation of isocyanate prepolymer: 10g of polyoxypropylene diamine was freeze-dried to obtain dehydrated polyoxypropylene diamine. The dehydrated polyoxypropylene diamine was slowly added dropwise to 3.42g of aromatic diisocyanate. After the addition was completed, the mixture was stirred in an ice-water bath for 2-3h, then transferred to an 85°C oil bath and heated in the oil bath for 3-4h to obtain an aromatic diisocyanate prepolymer.
[0068] (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: Take 1.63g of diethyltoluenediamine, freeze-dry it, slowly add it dropwise to the aromatic diisocyanate prepolymer, stir it for 30 minutes, then add the polyimide nanopowder and stir it for another 10 minutes. Transfer it to a mold, cure it in an oven, and cure it at 80°C for 48 hours or more to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0069] The mass fraction of polyimide in the prepared thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability is 0.1wt%.
[0070] In this example, polyimide and polyurea materials are directly mixed, and the mechanical properties of the obtained PUA-PI composite material are significantly reduced. The reason for this is that the dispersion of polyimide molecules in the PUA-PI composite material is poor, and the PI molecules and PUA molecules are mainly connected by weak interactions such as hydrogen bonds and van der Waals forces, and the bonding interface is low in tightness.
[0071] Comparative Example 4 A method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability comprises the following steps: (1) Preparation process of nano polyimide: Aromatic diamine is dissolved in butyrolactone, and pyromellitic anhydride is slowly added dropwise, and the mixture is placed in a 65°C oil bath for heating reaction for 2-3 hours, and then the mixture is taken out and placed in a mold, and then dried at 110°C for 8 hours or more for dehydration to obtain a polyimide solid; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is centrifuged to obtain a centrifuged upper layer liquid, and finally the centrifuged upper layer liquid is dried to obtain a polyimide nanopowder.
[0072] (2) Preparation of isocyanate prepolymer: Freeze-dry 10g of polyoxypropylene diamine to obtain dehydrated polyoxypropylene diamine. Mix 3.42g of 2,4'-MDI with 4,4'-MDI isomers and 0.015g of polyimide nanopowder. Slowly drop the dehydrated polyoxypropylene diamine into the aromatic diisocyanate. After the dropwise addition is completed, stir in an ice-water bath for 2-3h, then transfer to an 85℃ oil bath and heat in the oil bath for 3-4h to obtain a polyimide / aromatic diisocyanate composite prepolymer.
[0073] (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: Take 1.63g of diethyltoluenediamine and freeze-dry it. Slowly add the dehydrated diethyltoluenediamine dropwise into the polyimide / aromatic diisocyanate prepolymer, stir for 30 minutes and then transfer it to a mold. Curing it in an oven and curing it at 80°C for 48 hours or more to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0074] The mass fraction of polyimide in the prepared thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability is 0.1wt%.
[0075] In this example, no solvent was used to mix and disperse the aromatic diisocyanate and the polyimide. Obvious stratification occurred during the prepolymerization process, and a small amount of polyimide particles still existed after the prepolymerization. This indicated that the polyimide did not react fully with the aromatic diisocyanate.
[0076] Comparative Example 5 Purchase polyimide directly and grind it into powder.
[0077] A method for preparing a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability comprises the following steps: (1) Preparation process of nano polyimide: The purchased polyimide powder was put into a ball mill for ball milling at a speed of 500 rad for 8 h. The ball milled powder was taken out and dried to obtain polyimide nanopowder.
[0078] (2) Preparation of isocyanate prepolymer: Freeze-dry 10g of polyoxypropylene diamine to obtain dehydrated polyoxypropylene diamine. Mix 3.42g of 2,4'-MDI with 4,4'-MDI isomers and 0.015g of polyimide nanopowder. Slowly drop the dehydrated polyoxypropylene diamine into the aromatic diisocyanate. After the dropwise addition is completed, stir in an ice-water bath for 2-3h, then transfer to an 85℃ oil bath and heat in the oil bath for 3-4h to obtain a polyimide / aromatic diisocyanate composite prepolymer.
[0079] (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: Take 1.63g of diethyltoluenediamine and freeze-dry it. Slowly add the dehydrated diethyltoluenediamine dropwise into the polyimide / aromatic diisocyanate prepolymer, stir for 30 minutes and then transfer it to a mold. Curing it in an oven and curing it at 80°C for 48 hours or more to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
[0080] The mass fraction of polyimide in the prepared thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability is 0.1wt%.
[0081] This example uses purchased polyimide powder to modify the polyurea corrosion-resistant material, which has a large gap in purity compared with the thermally stable nano-polyimide prepared by the present invention. In addition, the purchased nano-polyimide has uneven particle size in the experiment, resulting in small-scale agglomeration of the composite material.
[0082] Test Example 1 of the Examples of the Invention and the Comparative Examples The performance test of thermally stable thermoplastic polyimide-polyurea corrosion-resistant materials includes the following test methods: (1) Impact strength test; First, an aluminum sheet with a size of 100mm×12.5mm×2mm was selected to test the impact strength of the empty aluminum sheet, record the energy value absorbed by the empty aluminum sheet sample, and calculate the impact strength. Then, the polyurea corrosion-resistant material obtained by the method in Example 1 was tested for impact strength. The polyurea corrosion-resistant material film was cut into a square film of 100mm×12.5mm with a cutter and adhered to one side of the aluminum sheet. The pure polyurea-aluminum sheet bond was tested for impact strength, and the energy value absorbed by the polyurea corrosion-resistant material sample was recorded and its impact strength was calculated. The two values were subtracted to calculate the impact strength of the polyurea corrosion-resistant material.
[0083] (2) Corrosion resistance test; The polyurea corrosion-resistant material was immersed in 50g / L H2SO4 solution, NaOH solution and NaCl solution for 30 days. The anti-swelling performance of the polyurea corrosion-resistant material after immersion was tested. In order to ensure the accuracy of the experimental data, 5 samples were prepared for each group of experiments, and the average value was taken for analysis. The polyurea corrosion-resistant material was taken out and weighed every two days, and the swelling rate of the material was calculated (see formula 1): Formula 1 in: W1——Swelling rate of polyurea corrosion resistant material; m2——initial weight of polyurea corrosion resistant material; m1——the weight of polyurea corrosion resistant material after immersion for N days; (3) Tensile strength test; The polyurea corrosion-resistant material obtained in Example 1 was subjected to a tensile strength test. The pure polyurea film was cut into 4 types of tensile standard parts with a punch. The width b and thickness h of the polyurea corrosion-resistant material tensile standard parts were measured using a vernier caliper. After inputting the length and width parameters, a tensile strength test was performed to obtain the stress-strain curve of the polyurea corrosion-resistant material.
[0084] (4) Thermogravimetric analysis test; The polyurea corrosion-resistant material obtained in Example 1 was subjected to a thermogravimetric analysis test. The polyurea corrosion-resistant material film was cut into a square film of 100 mm×12.5 mm and subjected to a thermogravimetric analysis test using a high-temperature differential thermal analyzer under nitrogen protection conditions.
[0085] The above test results are collated, and the experimental data of the impact strength performance of the thermally stable thermoplastic polyimide-polyurea corrosion-resistant material is shown in Figure 1 ,pass Figure 1 It can be concluded that with the increase of polyimide components, the tensile strength of thermoplastic polyimide-polyurea corrosion-resistant materials gradually increases. When the component is 0.8wt%, the tensile strength of thermoplastic polyimide-polyurea corrosion-resistant materials is the highest, which indicates that the polyimide molecules strengthen the hard segment in the polyurea molecular chain. After that, with the increase of components, the tensile strength of thermoplastic polyimide-polyurea corrosion-resistant materials shows a downward trend. This is because the increase in component content affects its dispersibility in the composite material; Corrosion resistance test data of thermally stable thermoplastic polyimide-polyurea corrosion resistant materials can be found in Figure 2 ,pass Figure 2 It can be seen that thermoplastic polyimide-polyurea corrosion-resistant materials have excellent corrosion resistance, among which acid corrosion resistance is the best, followed by salt corrosion resistance, and the worst is alkali corrosion resistance. Figure 2 From (a) and (b), it can be seen that the thermoplastic polyimide-polyurea corrosion-resistant material has better corrosion resistance than the polyurea material; The experimental data of tensile properties of thermally stable thermoplastic polyimide-polyurea corrosion-resistant materials can be found in Figure 3 ,pass Figure 3 It can be seen that as the component of polyimide nanopowder increases, the tensile strength and elongation at break of the thermoplastic polyimide-polyurea corrosion-resistant material are significantly improved, and the mechanical properties are the highest when the component is 0.8wt%. When the component increases again, the mechanical properties show a downward trend, which shows that excessive polyimide will affect the uniformity of the thermoplastic polyimide-polyurea corrosion-resistant material; Thermogravimetric analysis of thermally stable thermoplastic polyimide-polyurea corrosion-resistant materials Figure 4 ,pass Figure 4 It can be concluded that with the increase of the polyimide component in the composite material, the thermal weight loss of the composite material becomes less and less, which shows that the addition of polyimide molecules can significantly improve the thermal stability of thermoplastic polyimide-polyurea corrosion-resistant materials.
Claims
1. A thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability, characterized in that: It has the following structural formula: ; In the above formula: n is the average number of repeating units of polyimide, which is a positive integer; m is the average number of repeating units of polyurea, which is a positive integer; The structural formula of X is ; The structural formula of Y is .
2. The method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability according to claim 1, characterized in that: The process includes: (1) Preparation of polyimide nanopowder: The diamine monomer is dissolved in a solvent, and the dianhydride monomer is slowly added to obtain a high molecular weight polyamic acid through a polycondensation reaction, and then thermal imidization and dehydration are performed to form polyimide; the obtained polyimide solid is then ball-milled, and the ball-milled mixed liquid is solid-liquid separated to obtain an upper liquid, and finally the upper liquid is dried to obtain a polyimide nanopowder; (2) Preparation of isocyanate prepolymer: freeze-drying the amino-terminated polyether to obtain a dehydrated amino-terminated polyether; Dissolving diisocyanate and polyimide nanopowders in a solvent and uniformly dispersing them by ultrasonication to obtain a diisocyanate / polyimide mixed solution; The dehydrated amino-terminated polyether is slowly added dropwise to the diisocyanate / polyimide mixed solution, stirred in an ice water bath for 2-3 hours, and then transferred to 80-90° C. and heated for 3-4 hours to obtain a polyimide / diisocyanate composite prepolymer; (3) Preparation of thermoplastic polyimide-polyurea corrosion-resistant materials with thermal stability: The liquid amine chain extender is freeze-dried, and the dehydrated liquid amine chain extender is slowly added dropwise to the polyimide / diisocyanate composite prepolymer, reacted for more than 30 minutes, transferred to a mold, cured and solidified, to obtain a thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability.
3. The method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability according to claim 2, characterized in that: In the step (1), the dianhydride monomer is selected from one or a mixture of pyromellitic dianhydride and dianhydride; the diamine monomer is selected from one or a mixture of 4,4'-diaminodiphenyl ether and p-phenylenediamine; and the solvent is selected from butyrolactone.
4. The method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability according to claim 2, characterized in that: In the step (1), the temperature of the polycondensation reaction is 60-70°C, and the reaction time is 2-3 hours; and / or the drying temperature of the thermal imidization is 100-120°C, and the drying time is 8 hours or more.
5. The method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability according to claim 2, characterized in that: In the step (1), the ball milling treatment adopts a high-speed planetary ball mill, and the parameters are set as follows: revolution: rotation = 1:2, the ball milling speed is 350-550 rpm, and the material ball mass ratio is polyimide: solvent: ball milling ball = 1: (80-100): (200-300); And / or, the solid-liquid separation is centrifugal separation, and the centrifugation adopts a high-speed refrigerated centrifuge with a centrifugal speed of 5000-5500rpm.
6. The method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability according to claim 2, characterized in that: In the step (1), the particle size of the polyimide nanopowder is 50-500 nm.
7. The method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability according to claim 2, characterized in that: In the step (2), the amino-terminated polyether is polyoxypropylene diamine; and / or the diisocyanate is aromatic diisocyanate and / or aliphatic diisocyanate; and / or, in terms of mass ratio, thermoplastic polyurea: polyimide nanopowder = 100: (0.1-2.0).
8. The method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability according to claim 2, characterized in that: In the step (2), the ultrasonic dispersion time is more than 20 minutes; and / or the slow dripping speed is 0.1-0.5 mL / s.
9. The method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability according to claim 2, characterized in that: In the step (3), the liquid amine chain extender is diethyltoluenediamine.
10. The method for preparing the thermoplastic polyimide-polyurea corrosion-resistant material with thermal stability according to claim 2, characterized in that: In the step (3), the stirring time is more than 30 minutes; and / or the drying temperature is 80° C., and the curing time is 48 hours or more.
Citation Information
Patent Citations
Preparation method for soluble thermoplastic polyimide and ultrafine powder thereof
CN108192097A
Polyurea-polyimide random block copolymer as well as preparation method and application thereof
CN114854008A
Shape memory polyurea / polyimide compound and preparation method thereof
CN117247579A
Polyurethane composition, polyurethane adhesive and flexible copper-clad plate containing adhesive
CN117304438A
Method for manufacturing a safe, harmful-substance-decomposing sterilizing disinfectant using an inorganic mineral ionized alkaline composition
KR1020220129263A